Prospects for microbiome modulation in autoimmune diseases: a literature review - M. A. Peshkova; A. A. Korneev; P. I. Koteneva; N. V. Kosheleva; P. S. Timashev (Сеченовский вестник)
Autoimmune diseases are characterized by dysregulation of immune responses and damage to healthy body tissues. Their complete cure remains elusive, and existing therapies are often accompanied by side effects. Recent studies have shown a signifi cant role of disturbances in the composition of the microbiome in the development of autoimmune reactions. Moreover, modulation of the microbiome through various therapeutic interventions represents a promising direction in the framework of complex therapy of the underlying disease. Extracellular vesicles, in particular exosomes, transport biologically active substances between cells, and a number of studies have shown their therapeutic effect in autoimmune diseases. However, the role of extracellular vesicles in modulating the microbiome remains poorly understood, and further research is needed to better understand their impact on the pathogenesis of autoimmune diseases and associated microbiome changes, as well as to develop new treatment strategies. The presented literature review, based on a study of English-language sources, examines the importance of the microbiota of different loci of the human body (intestines, skin, oral cavity) in the development of autoimmune diseases such as multiple sclerosis, psoriasis and Sjögren’s disease. The role of extracellular vesicles in modulating the microbiome during autoimmune diseases therapy is discussed.